ASPEK PSIKOLOGIS DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH (MI) - Khotijah Khotijah (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Elementary school students include beginers in Arabic language learning. Besides, they are undergoing many changes physically and psikchologically. Arabic language learning at this level is the foundation layers of the next lesson. Therefore, teachers should pay attention to their psychological elements including interest, talent, level of intelligent, motivation, and cognitive development. It is intended to form a positif attitude of student to Arabic language. Elements of psychology should be considered when forming the material, media, and learning method. The material it teaches is listening, speaking, reading, and wraiting. But more speaking skills trough conversation and vocabulary recitations. The appropriate media is original object, picture, and artificial objects. As for the methods that children loved are playing method and singing method.